2009
DOI: 10.1074/jbc.m806452200
|View full text |Cite
|
Sign up to set email alerts
|

Heat-shock Protein 90 Is Essential for Stabilization of the Hepatitis C Virus Nonstructural Protein NS3

Abstract: The hepatitis C virus (HCV) is a major cause of chronic liver disease. Here, we report a new and effective strategy for inhibiting HCV replication using 17-allylaminogeldanamycin (17-AAG), an inhibitor of heat-shock protein 90 (Hsp90). Hsp90 is a molecular chaperone with a key role in stabilizing the conformation of many oncogenic signaling proteins. We examined the inhibitory effects of 17-AAG on HCV replication in an HCV replicon cell culture system. In HCV replicon cells treated with 17-AAG, we found that H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 47 publications
3
49
0
Order By: Relevance
“…Among chaperone proteins, Hsp90 has been implicated in HCV replication. Hsp90 is thought to enhance the maturation of the NS2/NS3 (40,49) and to form a complex with FKBP8 and NS5A to participate in HCV replication (44). This study demonstrated that Hsp72 chaperone activity could also increase levels of the replicase complex, leading to enhanced viral RNA relication.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Among chaperone proteins, Hsp90 has been implicated in HCV replication. Hsp90 is thought to enhance the maturation of the NS2/NS3 (40,49) and to form a complex with FKBP8 and NS5A to participate in HCV replication (44). This study demonstrated that Hsp72 chaperone activity could also increase levels of the replicase complex, leading to enhanced viral RNA relication.…”
Section: Discussionmentioning
confidence: 67%
“…Some of these proteins, such as hVAP-33 (41), FKBP8 (44), Hsp90 (40,44), and cyclophilin A (39), may participate directly in the replicase complex. Of these proteins, Hsp90 is a chaperone protein and cyclophilin A is a co-chaperone protein.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of the #50-1 HCV replicon cells with the Hsp90 inhibitor 17-AAG [8,16,17] suppresses HCV RNA replication and NS3 is the only HCV protein degraded in these cells [15]. This finding led us to suggest a crucial role for Hsp90-NS3 complexes in the HCV life cycle.…”
mentioning
confidence: 80%
“…Western blotting NNC#2 cells were seeded at 1.5×10 5 cells in 24-well plates, treated with 17-AAG alone, MG132 alone, or combined 17-AAG and MG132, and cultured for 48 h. Western blotting analysis was performed using a previously described method [15]. The primary antibodies were monoclonal or polyclonal antibodies against PSMA7 (Abcam, Cambridge, MA, USA) and β-actine (SIGMA, Sigma-Aldrich).…”
Section: Real-time Reverse Transcriptase Pcr Analysismentioning
confidence: 99%
See 1 more Smart Citation